(untitled) (Geologica Macedonica, 2013)
In this paper examples data is presenting from the mineral researches on couple of examples from moulding decoration (archeological finding) which is found on the Kockarnica at the ancient city Stobi. Point of the moulding fragments researches is specify if they are all natural stones from mineral origin or parts of them are synthetic. It is very important to give information for their geological origin, more specifically to give information about where we can find them. Results will serve first for making this artifact, but also for receiving information about its origin. With other words, we need to know whether the artifact is produced in Ancient Macedonia or it is brought from further places. Given results show that the biggest part of the examples originates from Macedonia only beryl appears as an exception.